4(y-3)+3=8(2y+5)

Simple and best practice solution for 4(y-3)+3=8(2y+5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(y-3)+3=8(2y+5) equation:


Simplifying
4(y + -3) + 3 = 8(2y + 5)

Reorder the terms:
4(-3 + y) + 3 = 8(2y + 5)
(-3 * 4 + y * 4) + 3 = 8(2y + 5)
(-12 + 4y) + 3 = 8(2y + 5)

Reorder the terms:
-12 + 3 + 4y = 8(2y + 5)

Combine like terms: -12 + 3 = -9
-9 + 4y = 8(2y + 5)

Reorder the terms:
-9 + 4y = 8(5 + 2y)
-9 + 4y = (5 * 8 + 2y * 8)
-9 + 4y = (40 + 16y)

Solving
-9 + 4y = 40 + 16y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-16y' to each side of the equation.
-9 + 4y + -16y = 40 + 16y + -16y

Combine like terms: 4y + -16y = -12y
-9 + -12y = 40 + 16y + -16y

Combine like terms: 16y + -16y = 0
-9 + -12y = 40 + 0
-9 + -12y = 40

Add '9' to each side of the equation.
-9 + 9 + -12y = 40 + 9

Combine like terms: -9 + 9 = 0
0 + -12y = 40 + 9
-12y = 40 + 9

Combine like terms: 40 + 9 = 49
-12y = 49

Divide each side by '-12'.
y = -4.083333333

Simplifying
y = -4.083333333

See similar equations:

| (3x-2y)+8=-15 | | 3x+6(-1)=-30 | | -1x+14= | | 3x^4+x^3+3x^2-29x-10=0 | | 5w+-2.5=-7.5 | | g-2=1/4(4g-2) | | 2B+40=240 | | x^3-7x^2+17x+5=0 | | 17x-9[x+4]=3x-26 | | 0.054x^2+x-0.4=0 | | 14=9+-x | | 14310=5.0625*h*3.14 | | 72-4-14d=36 | | 121.1=1.3-4d | | Tgx=0.04 | | 0=(X-54166)/10200 | | -3a^8+2a^6-a^2= | | 14310=5.0625*h*3.13 | | 3x+35x=15x+51 | | K^2x^2+2(x+1)x+4=0 | | 3x+9=-9-10x | | 2x^2+8+3=0 | | Y+3=0(x-3) | | 0=x-54166/10200 | | 3x+9=-69-9 | | 5cos=3 | | an-6an-1+8an-2=9 | | 8z-7=2 | | 33y=-145 | | (3x-2y)+7=0 | | 2x-125=45-8x | | 7.5a=6 |

Equations solver categories